2018
DOI: 10.1111/jsap.12968
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary‐focused assessment with sonography for trauma‐airway, breathing, circulation, disability and exposure: a prospective observational study in 64 canine trauma patients

Abstract: Objective: To describe the technique and findings of the 'veterinary focused assessment with sonography for trauma-airway, breathing, circulation, disability and exposure' protocol in dogs suffering from trauma. Materials and MethOds: Prospective observational study on a new point-of-care ultrasound protocol on 64 dogs suffering from trauma and comparison of findings with radiology. results: Comparison of the results of this new ultrasound protocol for trauma patients with radiography findings for pneumothorax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Thus, if the lung surface pathology is not present at these respective acoustic windows, then PC would be unidentified. Other LUS techniques describe a “sliding” protocol, where the ultrasound probe is slid in a dorsal‐ventral direction between intercostal spaces 19,24,25 . In theory, a sliding protocol allows for a more complete assessment of all possible lung acoustic windows and may have detected the missed PC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, if the lung surface pathology is not present at these respective acoustic windows, then PC would be unidentified. Other LUS techniques describe a “sliding” protocol, where the ultrasound probe is slid in a dorsal‐ventral direction between intercostal spaces 19,24,25 . In theory, a sliding protocol allows for a more complete assessment of all possible lung acoustic windows and may have detected the missed PC.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent study of dogs that sustained trauma documented that 100% of the dogs with PC identified on TXR had alveolarinterstitial syndrome on LUS (B-lines and C-lines) most consistent with PC. 25 In this study, dogs had LUS, standard 3-view TXR, and TCT imaging modalities acquired in a 30-minute time frame within 24 hours of sustaining motor vehicle trauma. The study hypotheses were: (1) LUS would have high sensitivity for diagnosis of PC compared to TCT; (2) LUS would correctly identify more dogs as positive for PC than TXR when compared to TCT; (3) LUS PC score would correlate to TCT PC score; and (4) interobserver agreement would be high for interpretation of LUS B-lines and C-lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified Armenise lung ultrasound protocol (3) was developed to evaluate the curtain sign at the caudal borders of the lung for pathology, to evaluate regions of the thorax where free air is most likely to accumulate (caudal dorsal thorax with the patient in sternal recumbency or standing, widest part of the thorax at the caudal border with patients in lateral recumbency), and to evaluate the ventral-most regions of the thorax for small volumes of pleural effusion that may not be identified when the probe remains perpendicular to the ribs (Figure 4). Dogs were scanned in sternal, right lateral, and left lateral recumbency as well as standing.…”
Section: Lung Ultrasound Protocolmentioning
confidence: 99%
“…The probe is then slid ventrally until the pleural line reappears (the most caudal dorsal region of the thorax). From this point, the remainder of the lung and pleural space is evaluated in a similar fashion as described by Armenise et al (3), with the exception that the curtain sign is identified again in the mid thorax and followed ventrally until it contacts the heart, at which point the probe is turned parallel to the ribs to evaluate the most ventral regions of the thorax for the presence of pleural effusion (Figure 4).…”
Section: Lung Ultrasound Protocolmentioning
confidence: 99%